The Harmony and Tension of Faith and Reason：A Probe into the View of "Faith" in Christianity - BAO, Yujie (Journal of Research for Christianity in China (JRCC), 2023)
The development of Christianity in the broadest sense has gone through a historical transition from Judaism and early Christianity (Catholicism) to Protestantism. During this process, although different believers at different times had faith in God, they found different ways of internalizing their faith and different answers to the question "How does God exist in their faith? In response to these two questions, this paper analyzes the relationship between faith and reason within Christianity, and the further development of the concept of faith in the Protestant Christian emphasis on "secular life," using the unexamined spirit of "faith" in Judaism as a comparative object. We also analyze the further development of the concept of faith in the Protestant Christian emphasis on "secular life. The shift in the position of "God" in the historical development of Judaism, early Christianity, and Protestantism.
Keywords: Christianity, Protestantism, Judaism, Faith, Conception of God